Hybrid models in Eastern Roman architecture: the example of the temple of Bel (Palmyra, Syria) - España-Chamorro, Sergio (Romanitas - Revista de Estudos Grecolatinos, 2019)
Cultural hybridisation in the Roman city of Palmyra is one of the most evident things for the ancient and modern visitor. Through one of the most famous monuments, the sacred complex of Bel, this paper provides any clues of interpretation in order to understand and to identify the cultural keys of its shape. This exam has been centred in some of its complex architecture and architectural decoration. All of this provides a social reading of this temple and go deep in some aspects about religious hybridisation and mixed social culture in the Roman province of Syria.
Keywords: Architecture; Hybridisation; Temple of Bel; Palmyra; Roman Syria